A systematic literature study of regression test case prioritization approaches - Dahiya, Omdev; Solanki, Kamna (International Journal of Engineering and Technology, 2018)
Regression testing is about running the entire test ensemble again to ensure that amendments do not negatively affect the system. A popular approach in regression testing is test case prioritization which reorders test cases in such a way that those with higher priorities are run earlier than those with lower priorities based on some criterion. Numerous researchers have worked on different aspects of prioritization approaches. This paper presents the result of the study conducted on different prioritization approaches showing mostly stressed areas by researchers and the areas where there is a future scope. For it, studies related to test case prioritization in regression testing from the year 2004 to 2018 are analyzed by dividing this time period into three slots of five years each. 36 studies were selected from 948 studies to answer the research questions framed for this study. The trends followed in TCP along with the approaches evolved are thus documented to find the current trends and future scope for the researchers to work upon. Â Â